The Effect of Using Cement Kiln Dust as a Partial Replacement of Cement on The Mechanical Properties of Concrete: Review and Modelling - Faraj, Nawdar Sabir; Hassun, Mahdi Osman (Kurdistan Journal of Applied Research, 2020)
There have been many efforts in reusing Cement Kiln Dust (CKD), a by-product of cement manufacturing, in various areas of civil works. These efforts have been made due to the necessity of the material for proper disposal, because of its very fine texture and the fact that if not handled properly, it will be harmful to human health and the environment. Numerous studies have been conducted to investigate the effects of incorporating CKD in concrete as an approach of reusing it. In the current study, the effect of using cement kiln dust on the mechanical properties of concrete as a partial replacement of cement was reviewed. The investigated mechanical properties were compressive strength for the curing ages of 7 and 28 days and tensile and flexural strengths, modulus of elasticity, and water absorption for the curing age of 28 days. It was concluded that replacing cement with CKD leads to detrimental effects on all mechanical properties of concrete. There were sufficient amount of data to establish correlations between the amount of cement replacement with CKD, and its effect on all mechanical properties of concrete except for water absorption. Regression analyses were performed and model equations with acceptably high R2s were prepared. The optimal CKD content regarding all mechanical properties was concluded to be 10% by the cement weight, at which 7 and 28 days compressive strengths, 28 days tensile and flexural strengths, and elastic modulus decreased by amounts of 11%, 12%, 8%, 9%, and 8% respectively.